What Are the Components of Interventions Focused on Quality-of-Life Assessment in Palliative Care Practice? A Systematic Review. Issue 4 (August 2016) - Catania, Gianluca; Beccaro, Monica; Costantini, Massimo; Timmins, Fiona; Zanini, Milko; Aleo, Giuseppe; Bagnasco, Annamaria; Sasso, Loredana
Abstract : Quality-of-life assessment is a central concept in palliative care. Clinical interventions focused on assessing quality of life are complex interventions. Current research is insufficient to determine how to implement interventions focused on quality-of-life assessment in palliative care. To explore the different components of interventions focused on quality-of-life assessment in palliative care, a systematic review and 5 databases were searched. Publications included were analyzed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) Framework Programme 7 practical guidance on using patient-reported outcome measurements in palliative care and the Quality of Life Assessment Principles in Palliative Care. Interventions and their components were identified and discussed. Identifying problems and monitoring change or response to treatment, screening for hidden problems, and facilitating communication were the 3 different types of intervention identified. None of the interventions fulfilled all the 11 Quality of Life Assessment Principles in Palliative Care. Overall, 6 characteristics of the components were identified: the quality-of-life measure, educational training, completing the measure (patients or proxy), collecting quality-of-life data (baseline and further assessment), identifying a coordinator, and presenting quality-of-life data. Because of heterogeneity of interventions, it is not possible to recommend 1 preferred intervention.